Paternal tyranny - Tarabotti, Arcangela (Other voice in early modern Europe., 2004)
Sharp-witted and sharp-tongued, Arcangela Tarabotti (1604-52) yearned to be formally educated and enjoy an independent life in Venetian literary circles. But instead, at sixteen, her father forced her into a Benedictine convent. To protest her confinement, Tarabotti composed polemical works exposing the many injustices perpetrated against women of her day. Paternal Tyranny, the first of these works, is a fiery but carefully argued manifesto against the oppression of women by the Venetian patriarchy. Denouncing key misogynist texts of the era, Tarabotti shows how despicable it was for Venice, a.